Fault test cases for series compensated transmission line with capacitor at line terminal - Md Tanbhir (Royal Institute of Technology, 2021)
This data set contains time series data of different simulated fault cases in high voltage series compensated transmission lines. The simulation is done in PSCAD using the Python automation library. The capacitor is located at one of the line terminals with CT and VT. The modelled line is 500 kV and 200 km long. The simulation is run for 1 second with 10 kHz sampling rate.

Each file contains 7 data in the following order,


Time

Voltage phase A

Voltage phase B

Voltage phase C

Current phase A

Current phase B

Current phase C

The variables used to study different test cases are shown below,


Fault inception angle (phase A): 0 and 90 degree

Source impedance ratio: 0.20 and 0.35

Capacitor level: 94 µF(50%), 78 µF(60%), 67 µF(70%)

Fault resistance: 0.10, 10, 20, 30 ohm

Fault location: 10 km reverse, 10 km, 50 km, 100 km, 125 km, 150 km, 155 km, 160 km. 165 km, 170 km, 180 km, 190 km

Fault type: No-fault, AG, BG, CG, ABG, CAG, BCG, ABCG, AB, CA, BC, ABC

All these factors lead to 6912 test cases in total. The test cases are organized in four (4) zipped folders each containing 1728 test cases. The PSCAD model file and an example python script that can be used to automate the simulations are also included herewith for anyone interested to replicate the results.

The name of the folder contains the information regarding fault inception angle and source impedance ratio for all test cases inside that folder, for example, the folder name Outputs_0_0.20 can be decoded as,

0: Fault inception angle (phase A)
0.20: Source impedance ration

The files names inside the folders include information about the other variables used in generating the test case. For example, the name test_f_10_0_67_0.01 can be interpreted as,

test_f: f for forward fault, r for reverse fault
10: fault location, 10 km
0: Fault type
67: Compensation level
0.01: Fault resistance

Fault types are interpreted as in PSCAD.

0 = No-Fault,
1 = Phase A to Ground
2 = Phase B to Ground
3 = Phase C to Ground
4 = Phase AB to Ground
5 = Phase AC to Ground
6 = Phase BC to Ground
7 = Phase ABC to Ground
8 = Phase AB
9 = Phase AC
10 = Phase BC
11 = Phase ABC

The different line parameters used in the PSCAD model is as below,

Conductor

Type: Chukar
Geometric mean radius: 20.345 mm
DC resistance: 0.0318Ω/km
Strands: 84
Strand radius: 1.8491 mm
Relative permeability: 1.0
Sag: 12 m
Height: 22 m
Sub-conductor: 2
Sub-conductor spacing: 0.4572 m
Ground wire number: 2
Radius: 5.5245 mm
DC resistance: 2.8645Ω/km
Relative permeability: 1.0
Sag: 10 m
Height: 10 m

Impedance

Positive sequence0.018 +j0.339 Ω/km
Zero sequence0.266 +j1.017 Ω/km

These simulations were run for assessing time-domain protections. Therefore, the parallel CB protection across the series capacitor is disabled, as one can safely assume even with the highest current levels, the CB will take at least 20 ms to operate. This is higher than the time limits for time-domain protection.

This work was funded through SweGRIDS, by the Swedish energy agency, Hitachi ABBPower Grids and the Swedish transmission network operator Svenska kraftnät.
Keywords: fault data; series compensation; time series; PSCAD; transmission line; series compensated line; Electrical Engineering, Electronic Engineering, Information Engineering; Elektroteknik och elektronik